Hypertrophic osteopathy in a cat with a concurrent injection-site sarcoma. Issue 2 (4th July 2015) - Salgüero, Raquel; Demetriou, Jackie; Constantino-Casas, Fernando; Herrtage, Michael
Case summary An 11-year old neutered female domestic shorthair cat presented for investigation of a large, partially ulcerated skin mass in the area of the left scapula. The cat had been vaccinated 6 weeks previously in the same area. Haematology showed a marked neutrophilia and monocytosis. Tru-cut biopsies were taken and histopathology was consistent with a high-grade soft tissue sarcoma. Thoracic radiographs and abdominal ultrasound revealed no abnormalities. Moderate mixed (palisading, brush border and smooth) periosteal reaction was seen on the diaphysis of long bones at the time of the radiographic examination. Magnetic resonance imaging of the mass showed infiltration within deeper tissues and the owners elected euthanasia. Post-mortem examination confirmed the presence of hypertrophic osteopathy with a concurrent injection-site sarcoma. No evidence of intra-thoracic or intra-abdominal disease was found. Relevance and novel information To our knowledge, this is the first report where hypertrophic osteopathy has been described in a cat with a soft tissue sarcoma, most likely an injection-site sarcoma.